Functionalized silicon dioxide modified nylon anti-aging solid coating and preparation method thereof
By modifying nano silica multi-layer structure, functionalized silica-modified nylon anti-aging solid coatings were prepared, which solved the problems of low mechanical properties and weak anti-aging ability of nylon coatings, and achieved better mechanical properties and anti-aging effects.
Patent Information
- Application Number
- CN202411785932.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nylon coatings have low mechanical properties and weak anti-aging ability, and are prone to aging and degradation when exposed to ultraviolet radiation.
Functionalized silica-modified nylon anti-aging solid coating was prepared by modifying nanosilicon dioxide. The coating is modified by multi-layer structure such as isocyanate-based nanosilica, chlorobutyl nanosilica, tetramethylpiperidine-based nanosilica and benzophenone tetramethylpiperidine-based nanosilica, etc. , enhances its mechanical properties and anti-aging ability.
It significantly improves the mechanical properties and anti-aging properties of the coating, can effectively resist ultraviolet radiation, and extend the service life of nylon coatings.
Smart Images

Figure CN119391291A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a functionalized silicon dioxide modified nylon anti-aging solid coating and a preparation method thereof. Background Art
[0002] Polymer materials have excellent thermal insulation, electrical insulation, processability and other characteristics, and are widely used as decorative and functional materials in industrial and agricultural production. However, due to defects and impurities introduced during the processing, most polymer materials are often prone to aging and degradation when exposed to sunlight, which not only destroys the appearance and performance of the polymer materials, but also shortens their service life. Therefore, it is of great significance to prevent polymer materials from aging and degradation caused by ultraviolet radiation. In current research, in order to protect polymer materials from ultraviolet damage, a typical and effective method is to use coatings containing ultraviolet absorbers. Nylon coating is one of the most important coatings at present and is widely used on polymer surfaces. The modification of the ultraviolet absorber added thereto is the most important anti-aging modification direction, and researchers have done a lot of research on this.
[0003] The patent of Chinese patent publication number CN103613966B discloses an anti-aging waterproof coating, and the patent of Chinese patent publication number CN103965738A discloses an anti-aging composite coating. Although both improve the anti-aging ability of the coating, they still have the problems of high addition amount and poor anti-aging effect. Nano-silicon dioxide has been widely used as the main component of ultraviolet absorbers due to its advantages of being non-toxic, environmentally safe and low cost, and can be transformed into various sizes and shapes. However, the anti-aging ability increased by adding nano-silicon dioxide alone is low, so it needs to be modified. Benzophenone is a UV absorber with a wide range of applications. Due to its wide UV absorption spectrum, they are protected from the effects of ultraviolet radiation, so they are used as flavoring ingredients, flavoring agents and additives in plastics, coatings, cleaning products and medicines. Hindered amines are organic amine compounds with steric hindrance ability, which have a good inhibitory effect on the photoinduced degradation of polymers and organic compounds. Moreover, studies have found that hindered amines can act synergistically with UV absorbers such as benzophenone derivatives to increase the anti-aging ability of UV absorbers. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a functionalized silica-modified nylon anti-aging solid coating and a preparation method thereof, which solves the problems of low mechanical properties and weak anti-aging ability of nylon coatings.
[0005] To achieve the above object, the present invention provides the following technical solution: a functionalized silica-modified nylon anti-aging solid coating, wherein the preparation method of the functionalized silica-modified nylon anti-aging solid coating comprises the following steps: (1) According to the mass ratio of 100:2500-6000:80-200, nano-silica is ultrasonically dispersed in a toluene solvent, and then 2,4-diisocyanatotoluene is added under a nitrogen atmosphere, stirred evenly, and reacted at 60-100° C. for 8-20 hours. After the reaction is completed, the mixture is filtered and washed with deionized water to obtain isocyanate-based nano-silica; (2) ultrasonically dispersing isocyanate-based nano-silica in tetrahydrofuran solvent, and then adding 2-chlorobutanol and a catalyst dibutyltin dilaurate under a nitrogen atmosphere, stirring evenly, and reacting. After the reaction is completed, filtering, and washing with deionized water to obtain chlorobutyl nano-silica; (3) ultrasonically dispersing chlorobutyl nano-silica in a mixed solvent of dichloromethane and toluene, then adding potassium iodide, stirring evenly, adding 4-amino-2,2,6,6-tetramethylpiperidine, reacting, filtering after the reaction is completed, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) Ultrasonic dispersion of tetramethylpiperidinyl nanosilica in dichloromethane, and then adding 20 H 20 O6 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy) benzophenone, after being stirred evenly, reacted to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving the nylon powder, the powder is mixed evenly with benzophenone-based tetramethylpiperidinyl-based nano-silica and a phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating.
[0006] Preferably, in step (2), the mass ratio of isocyanate-based nano-silica, tetrahydrofuran, 2-chlorobutanol and dibutyltin dilaurate is 100:2500-8000:120-300:4-10.
[0007] Preferably, in step (2), the reaction temperature is 80-120° C. and the reaction time is 12-36 h.
[0008] Preferably, in step (3), the mass ratio of chlorobutyl nano-silica, dichloromethane, toluene, potassium iodide and 4-amino-2,2,6,6-tetramethylpiperidine is 100:2500-8000:1500-6000:12-30:35-90.
[0009] Preferably, in step (3), the reaction temperature is 50-80° C. and the reaction time is 6-15 h.
[0010] Preferably, in step (4), the mass ratio of tetramethylpiperidinyl nano-silica, dichloromethane and 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone is 100:1500-4000:25-60.
[0011] Preferably, in step (4), the reaction temperature is 20-40° C. and the reaction time is 3-8 h.
[0012] Preferably, in step (5), the mass ratio of nylon, benzophenone-based tetramethylpiperidinyl nano-silica and phenolic antioxidant is 100:1.5-5:0.1-0.3.
[0013] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The functionalized silica-modified nylon anti-aging solid coating comprises the following steps: firstly, the isocyanate group of isocyanate-based nano-silica is reacted with the hydroxyl group of 2-chlorobutanol to obtain chlorobutyl nano-silica; then, potassium iodide is used as a catalyst to react the chlorine atom of the chlorobutyl nano-silica with the amino group of 4-amino-2,2,6,6-tetramethylpiperidine to obtain tetramethylpiperidinyl nano-silica; then, the imine group of the tetramethylpiperidinyl nano-silica is subjected to addition reaction with 2-hydroxy-4-(3-methylacrylate-2-hydroxypropoxy)benzophenone to obtain benzophenone-based tetramethylpiperidinyl nano-silica; and finally, nylon is used as a matrix and benzophenone-based tetramethylpiperidinyl nano-silica is used as a modifier to prepare the functionalized silica-modified nylon anti-aging solid coating through mechanical blending.
[0014] The functionalized silica-modified nylon anti-aging solid coating has better mechanical properties and anti-aging properties than pure nylon solid coating. The addition of nano-silicon dioxide in the coating not only improves the mechanical properties of the coating, but also increases the anti-aging ability of the coating. Due to the nano-scale and structure of the nano-silicon dioxide, it has a nano-size effect. When irradiated with ultraviolet light, it has good light stability, not only has good interface reflection ability, but also will not decompose and change color. The nylon coating improves the anti-aging ability of the nylon coating through the reflection and diffuse reflection of ultraviolet light by the nano-silicon dioxide. The nano-silicon dioxide has good mechanical properties. The addition of nano-silicon dioxide in the nylon coating Silicon dioxide, through the organic-inorganic network structure formed by nano-silicon dioxide and the matrix, disperses the external stress and increases the mechanical properties of the coating. The benzophenone molecular derivative has good ultraviolet absorption ability. The internal hydrogen bond formed by the carbonyl and hydroxyl groups in the molecule constitutes a six-membered ring in the molecule. When exposed to ultraviolet light, the six-membered ring breaks due to thermal movement, and the absorbed ultraviolet energy is dissipated and removed in the form of heat energy, thereby achieving the purpose of anti-aging. In addition, the hindered amine molecular group can achieve a synergistic effect by grafting with the benzophenone derivative, increasing the ultraviolet absorption and anti-aging ability of the benzophenone derivative. Grafting small molecules on inorganic substances can not only enable a synergistic effect between the two, but also increase the stability of the small molecules, making the nylon coating more stable in anti-aging. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is the reaction formula of chlorobutyl nano-silica and 4-amino-2,2,6,6-tetramethylpiperidine; Figure 2 It is a reaction formula of tetramethylpiperidinyl nano-silica and 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone. DETAILED DESCRIPTION
[0016] To achieve the above object, the present invention provides the following specific implementation methods and examples: A functionalized silica-modified nylon anti-aging solid coating, the preparation method of which comprises the following steps: (1) According to the mass ratio of 100:2500-6000:80-200, nano-silica is ultrasonically dispersed in a toluene solvent, and then 2,4-diisocyanatotoluene is added under a nitrogen atmosphere, stirred evenly, and reacted at 60-100° C. for 8-20 hours. After the reaction is completed, the mixture is filtered and washed with deionized water to obtain isocyanate-based nano-silica; (2) ultrasonically dispersing isocyanate-based nano-silica in tetrahydrofuran solvent at a mass ratio of 100:2500-8000:120-300:4-10, and then adding 2-chlorobutanol and catalyst dibutyltin dilaurate under a nitrogen atmosphere, stirring evenly, reacting at 50-80°C for 6-15h, filtering after the reaction is completed, and washing with deionized water to obtain chlorobutyl nano-silica; (3) ultrasonically dispersing chlorobutyl nano-silica in a mixed solvent of dichloromethane and toluene at a mass ratio of 100:2500-8000:1500-6000:12-30:35-90, then adding potassium iodide, stirring evenly, adding 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 50-80°C for 6-15h, filtering after the reaction, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) According to the mass ratio of 100:1500-4000:25-60, tetramethylpiperidinyl nano-silica is ultrasonically dispersed in dichloromethane, and then a molecule with the molecular formula C is added. 20 H 20 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 is stirred evenly and reacted at 20-40°C for 3-8h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving the nylon powder according to the mass ratio of 100:1.5-5:0.1-0.3, the powder was mixed evenly with benzophenone-based tetramethylpiperidinyl nano-silica and phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating. Example 1
[0017] (1) Ultrasonic dispersion of 5 g of nano-silica in 125 g of toluene solvent was performed, and then 4 g of 2,4-diisocyanatotoluene was added under a nitrogen atmosphere. After stirring, the mixture was reacted at 60 °C for 8 h. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain isocyanate-based nano-silica. (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 100 g of tetrahydrofuran solvent, and then 4.8 g of 2-chlorobutanol and 0.16 g of dibutyltin dilaurate catalyst were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 50 ° C for 6 h. After the reaction was completed, it was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 62.5 g of dichloromethane and 37.5 g of toluene, and then adding 0.3 g of potassium iodide. After stirring evenly, adding 0.875 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 50 ° C for 6 h, after the reaction is completed, filtering, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) 2 g of tetramethylpiperidinyl nano-silica was ultrasonically dispersed in 30 g of dichloromethane, and then 0.5 g of a compound with the molecular formula C was added. 20 H 20 2-Hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 was stirred evenly and reacted at 20°C for 3h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving 8 g of nylon powder, 0.12 g of benzophenone-based tetramethylpiperidinyl nano-silica and 0.008 g of phenolic antioxidant were mixed evenly in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating. Example 2
[0018] (1) Ultrasonic dispersion of 5 g of nano-silica in 150 g of toluene solvent, and then adding 5 g of 2,4-diisocyanatotoluene in a nitrogen atmosphere, stirring evenly, and reacting at 70 ° C for 10 h. After the reaction is completed, filtering, washing with deionized water, and obtaining isocyanate-based nano-silica; (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 150 g of tetrahydrofuran solvent, and then 6 g of 2-chlorobutanol and 0.2 g of dibutyltin dilaurate catalyst were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 55 °C for 8 h. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 80 g of dichloromethane and 50 g of toluene, then adding 0.35 g of potassium iodide, stirring evenly, adding 1 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 55 °C for 8 h, filtering after the reaction, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) 2 g of tetramethylpiperidinyl nano-silica was ultrasonically dispersed in 40 g of dichloromethane, and then 0.6 g of a compound with the molecular formula C was added. 20 H 20 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 was stirred evenly and reacted at 25°C for 4h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving 8 g of nylon powder, 0.16 g of benzophenone-based tetramethylpiperidinyl nano-silica and 0.01 g of phenolic antioxidant were mixed evenly in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating. Example 3
[0019] (1) Ultrasonic dispersion of 5 g of nano-silica in 200 g of toluene solvent, and then adding 7 g of 2,4-diisocyanatotoluene under a nitrogen atmosphere, stirring evenly, and reacting at 80 ° C for 14 h. After the reaction is completed, filtering, washing with deionized water, and obtaining isocyanate-based nano-silica; (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 200 g of tetrahydrofuran solvent, and then 7 g of 2-chlorobutanol and 0.25 g of dibutyltin dilaurate catalyst were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 65 ° C for 10 h. After the reaction was completed, it was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 120 g of dichloromethane and 80 g of toluene, then adding 0.55 g of potassium iodide, stirring evenly, adding 1.4 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 65 ° C for 11 h, after the reaction is completed, filtering, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) 2 g of tetramethylpiperidinyl nano-silica was ultrasonically dispersed in 55 g of dichloromethane, and then 0.8 g of a compound with the molecular formula C was added. 20 H 20 2-Hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 was stirred evenly and reacted at 30°C for 5h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving, 8 g of nylon powder was mixed evenly with 0.3 g of benzophenone-based tetramethylpiperidinyl nano-silica and 0.016 g of phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating. Example 4
[0020] (1) Ultrasonic dispersion of 5 g of nano-silica in 260 g of toluene solvent was performed, and then 8 g of 2,4-diisocyanatotoluene was added under a nitrogen atmosphere. After stirring, the mixture was reacted at 90 °C for 18 h. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain isocyanate-based nano-silica. (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 280 g of tetrahydrofuran solvent, and then 10 g of 2-chlorobutanol and 0.32 g of catalyst dibutyltin dilaurate were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 70 ° C for 12 h. After the reaction was completed, it was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 160 g of dichloromethane and 120 g of toluene, then adding 0.65 g of potassium iodide, stirring evenly, adding 2 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 70 ° C for 14 h, after the reaction is completed, filtering, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) Ultrasonic dispersion of 2 g of tetramethylpiperidinyl nanosilica in 30-80 g of dichloromethane, and then adding 1 g of C 20 H 20 2-Hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 was stirred evenly and reacted at 35°C for 7h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving, 8 g of nylon powder was mixed evenly with 0.32 g of benzophenone-based tetramethylpiperidinyl nano-silica and 0.02 g of phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating. Example 5
[0021] (1) Ultrasonic dispersion of 5 g of nano-silica in 300 g of toluene solvent, and then adding 10 g of 2,4-diisocyanatotoluene under nitrogen atmosphere, stirring evenly, and reacting at 100 °C for 20 h. After the reaction is completed, filtering, and washing with deionized water to obtain isocyanate-based nano-silica; (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 320 g of tetrahydrofuran solvent, and then 12 g of 2-chlorobutanol and 0.4 g of dibutyltin dilaurate catalyst were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 80 ° C for 15 h. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 200 g of dichloromethane and 150 g of toluene, then adding 0.75 g of potassium iodide, stirring evenly, adding 2.25 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 80 ° C for 15 h, after the reaction is completed, filtering, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) 2 g of tetramethylpiperidinyl nanosilica was ultrasonically dispersed in 80 g of dichloromethane, and then 1.2 g of a compound with the molecular formula C was added. 20 H 20 2-Hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone of O6 was stirred evenly and reacted at 40°C for 8h to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving, 8 g of nylon powder was mixed evenly with 0.4 g of benzophenone-based tetramethylpiperidinyl nano-silica and 0.024 g of phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating.
[0022] Comparative Example 1 (1) Ultrasonic dispersion of 5 g of nano-silica in 180 g of toluene solvent, and then adding 6 g of 2,4-diisocyanatotoluene in a nitrogen atmosphere, stirring evenly, and reacting at 80 ° C for 12 h. After the reaction is completed, filtering, washing with deionized water, and obtaining isocyanate-based nano-silica; (2) 4 g of isocyanate-based nano-silica was ultrasonically dispersed in 200 g of tetrahydrofuran solvent, and then 9 g of 2-chlorobutanol and 0.24 g of catalyst dibutyltin dilaurate were added under a nitrogen atmosphere. After stirring evenly, the mixture was reacted at 60 ° C for 12 h. After the reaction was completed, it was filtered and washed with deionized water to obtain chlorobutyl nano-silica; (3) Ultrasonic dispersion of 2.5 g of chlorobutyl nano-silica in a mixed solvent of 120 g of dichloromethane and 100 g of toluene, then adding 0.45 g of potassium iodide, stirring evenly, adding 1.2 g of 4-amino-2,2,6,6-tetramethylpiperidine, reacting at 60 ° C for 12 h, after the reaction is completed, filtering, and washing with deionized water to obtain tetramethylpiperidinyl nano-silica; (4) After sieving, 8 g of nylon powder was mixed with 0.36 g of tetramethylpiperidinyl nano-silica and 0.02 g of phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating.
[0023] Under lightless conditions, the mechanical properties of functionalized silica modified nylon anti-aging solid coatings were tested in accordance with the national standard GB / T 29284-2012.
[0024]
[0025] After 3 days of illumination, the mechanical properties of the functionalized silica-modified nylon anti-aging solid coating were tested in accordance with the national standard GB / T 29284-2012.
[0026]
Claims
1. A functionalized silica-modified nylon anti-aging solid coating, characterized in that: The preparation method of the functionalized silica-modified nylon anti-aging solid coating comprises the following steps: (1) According to the mass ratio of 100:2500-6000:80-200, nano-silica is ultrasonically dispersed in a toluene solvent, and then 2,4-diisocyanatotoluene is added under a nitrogen atmosphere, stirred evenly, and reacted at 60-100° C. for 8-20 hours. After the reaction is completed, isocyanate-based nano-silica is obtained; (2) ultrasonically dispersing isocyanate-based nano-silica in tetrahydrofuran solvent, and then adding 2-chlorobutanol and a catalyst dibutyltin dilaurate under a nitrogen atmosphere, stirring evenly, and reacting. After the reaction is completed, chlorobutyl nano-silica is obtained; (3) ultrasonically dispersing chlorobutyl nano-silica in a mixed solvent of dichloromethane and toluene, then adding potassium iodide, stirring evenly, adding 4-amino-2,2,6,6-tetramethylpiperidine, and reacting. After the reaction is completed, tetramethylpiperidinyl nano-silica is obtained; (4) Ultrasonic dispersion of tetramethylpiperidinyl nanosilica in dichloromethane, and then adding 20 H 20 O6 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy) benzophenone, after being stirred evenly, reacted to obtain benzophenone-based tetramethylpiperidin-based nano-silica; (5) After sieving the nylon powder, the powder is mixed evenly with benzophenone-based tetramethylpiperidinyl-based nano-silica and a phenolic antioxidant in an ultra-speed blender, and then melt-extruded, tableted, air-cooled, ground and sieved to obtain a functionalized silica-modified nylon anti-aging solid coating.
2. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (2), the mass ratio of isocyanate-based nano-silica, tetrahydrofuran, 2-chlorobutanol and dibutyltin dilaurate is 100:2500-8000:120-300:4-10.
3. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (2), the reaction temperature is 80-120° C. and the reaction time is 12-36 hours.
4. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (3), the mass ratio of chlorobutyl nano-silica, dichloromethane, toluene, potassium iodide and 4-amino-2,2,6,6-tetramethylpiperidine is 100:2500-8000:1500-6000:12-30:35-90.
5. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (3), the reaction temperature is 50-80°C and the reaction time is 6-15h.
6. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (4), the mass ratio of tetramethylpiperidinyl nano-silica, dichloromethane and 2-hydroxy-4-(3-methacrylate-2-hydroxypropoxy)benzophenone is 100:1500-4000:25-60.
7. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (4), the reaction temperature is 20-40° C. and the reaction time is 3-8 h.
8. The functionalized silica-modified nylon anti-aging solid coating according to claim 1, characterized in that: In the step (5), the mass ratio of nylon, benzophenone-based tetramethylpiperidinyl nano-silica and phenolic antioxidant is 100:1.5-5:0.1-0.3.
Citation Information
Patent Citations
A kind of anti-aging waterproof coating
CN103613966B
Anti-ageing composite paint
CN103965738A